meμ: unifying application modeling and cluster exploitation - Alves, Albano (2004)
The increasing complexity of high-demand long-running applications has faced programmers with the need to take into account both development hardness and execution time. meu provides the flexibility to control the amount of computational and communication power being used in order to maximize resources utilization and to deliver high performance. In this paper we focus on the aspects of the paradigm that go beyond traditional message passing approaches, promoting the idea that by raising the abstraction level of programming models, programmers will make better use of the available resources with clear impact on both productivity and performance. We introduce the resource as the abstraction used to represent and manage both physical resources – nodes, memory, processors and communication technologies – and logical resources – modules, processes, tasks, threads, groups, etc. We also concentrate on the task of specifying, locating and aggregating resources in order to support the mapping of applications into the target cluster hardware and the explicit management of memory hierarchy.